Experimental Murine Teratomas - Butler, Patricia Cranmer Alberta (My University, 1974)
Early in the development of the embryo, cells lose their ability to differentiate into any adult type of cell and become determined. A cell which has achieved a certain degree of differentiation can ultimately reproduce to form only a limited number of cell types along the original line of differentiation: for example, a primitive mesenchymal cell can give rise to only connective tissues such as muscle or bone.
Apart from the primordial germ cells (those cells which later give rise to oocytes in the female and spermatocytes in the male), all cells have begun to specialize, with a consequent narrowing of their potential, very early in gestation.
Teratomas are neoplasms which contain many kinds of tissues which are foreign to the organ in which they arise. There is controversy over whether these tumours arise from the growth of cells which have escaped early developmental controls, or whether they arise from the proliferation of the only multipotential cell in the body, the germ cell. Rather than following their normal path of differentiation to oocytes or spermatocytes, they might fulfil their potential to form almost any kind of tissue. Thus tumours composed of skin, bone, muscle, nervous tissue, and glands are found in adult testes and ovaries.
Since the germ cells arise in the embryonic yolk sac and travel up the umbilical cord to the developing gonads, there is a theory that these multipotential cells may occasionally become lost and much later, often in adulthood, begin their proliferation in sites along the midline: at the base of the spine, in the chest and throat.
The experiments in this thesis explore an animal model in which teratomas can be produced by the grafting of 7½-day mouse embryos to the gonads of adult hosts. According to the literature the tumour which develops as a result of this operation is identical to those arising spontaneously in a highly inbred strain of mouse. Those experimental tumours which contain areas of undifferentiated tissues can be transplanted to other hosts; sometimes retaining their embryonic nature for many generations.
Whole embryos develop as teratomas in up to 80% of grafts to male hosts. The embryos can be cut in such a way that one half contains extra-embryonic material (that which eventually forms the placenta) and also the yolk sac containing the germ cells, and the other half which contains only sonatic tissue.
Grafts of the somatic parts result in teratomas in 74% of the testes, a rate similar to tumours from whole embryos, whereas grafts of the extra-embryonic parts containing germ cells resulted in only 1 small teratoma out of 35 grafts.
In this experimental model, it has been demonstrated that the primordial germ cells of the embryo are not responsible for the development of the neoplasms, but rather it is the somatic cells which are giving rise to these tumours. One must ask whether the controls which govern normal differentiation may become faulty and allow somatic cells to retain or regain their pluripotential nature making it possible, when conditions are right, to proliferate to form the "monstrous" tumour, teratoma.
Keywords: Medical Sciences; Medical Sciences